Childhood nephrotic syndrome in tropical Africa: then and now (2017)
This descriptive and comparative review examines the changing epidemiology, treatment, renal and patient outcome of childhood nephrotic syndrome (NS) in tropical Africa (TpAfr). In the 1960s to 1980s, corticosteroid-resistant non-minimal change disease (nMCD) including quartan malaria nephropathy (QMN) was the dominant renal histopathology type. The overall incidence of NS was 0.35–1.34% of hospital admissions. Median age at onset of NS ranged between 4.0 and 12.0 years while the mean (SD) age range was 5.8 (3.8) to 10.3 (4.8) years across studies. The male: female ratio was 1.6:1.0. The overall mean (SD) incidence of idiopathic minimal change disease (MCD) [21.6 (18.6%)] compared with idiopathic nMCD [59.1 (25.7%)] demonstrates significant dominance of the latter (p = 0.0001). Post-1989, the following mean (SD) incidences of histopathological types were: MCD 20.4 (17.7%), focal segmental glomerulosclerosis 39.0 (26.3%), membranoproliferative glomerulonephritis 25.4 (16.8%), proliferative glomerulonephritis 16.7 (27.0%) and membranous nephropathy 7.4 (4.5%). While the mean (SD) proportion of steroid resistance (SR) [73.5 (19.2%)] was significantly greater than the mean complete remission (CR) [26.5 (19.2%)] during 1960-1989 (p=0.005), mean (SD) SR [27.4 (25.3%)] was significantly lower than mean (SD) CR [66.1 (28.0%)] post-1989 (p < 0.001). Unlike QMN, hepatitis B virus, HIV infection, sickle cell disease and systemic lupus erythematosus are now increasingly being associated with NS in TpAfr. Mean (SD) renal survival post-1989 was 58.3 (37.0%) while all-cause mortality was 9.8%. Children with NS now survive better than before, reflecting improved access to healthcare and transition to a clinical pattern favouring idiopathic NS and increased sensitivity to corticosteroids.